Capital Market Integration and MiFID Implementation : The Bulgarian Experience - Byskov, Steen (World Bank, Washington, DC, 2013)
This note aims to assess the implementation of the Markets in Financial Instruments Directive (MiFID) in Bulgaria, provide an initial view on the impact it had on the Bulgarian securities markets, and draw lessons from the experience. Bulgaria entered the European Union (EU) and adopted MiFID at the cusp of a global crisis that hit central Europe particularly hard. MiFID implementation in Bulgaria began along with other EU countries on November 1st 2007, less than a year after Bulgaria had entered the union. Important changes for the local market were the introduction of the passport, which allows intermediaries to operate throughout Europe under the local license, a more competitive environment for trading venues as shares listed on the regulated market (RM) shares can be traded anywhere in Europe, and greater role for home supervisor.